Imaging of CT colonography : a pictorial review - Che Mohamed, Siti Kamariah; Abdul Rashid, Mohd Amran; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Mat Hassan, Mohd. Zailani; Md Nor, Azmi; Mohd Yusof, Mubarak; Abdul Rahman, Zainun (2011)
Computed Tomography Colonography (CTC), also referred to as virtual colonoscopy is a new diagnostic technique that uses special software to simulate conventional endoscopy. CTC uses data from Computed Tomography (CT) to generate two- and fly-through endoluminal three-dimensional images of the colon and rectum. CTC is an alternative to colonoscopy for diagnostic purposes in symptomatic patients with contraindications to conventional colonoscopy, and when the colonoscopy cannot be completed due to some reasons. The common imaging features of CTC were presented in this pictorial review.